2020
DOI: 10.1049/hve.2019.0193
|View full text |Cite
|
Sign up to set email alerts
|

Improved space charge transport model in bi‐layer dielectrics—considering carrier dynamic equilibrium

Abstract: The Maxwell-Wagner model and bipolar charge transport model both aim at describing the charge transport behaviours in dielectrics. The Maxwell-Wagner model performs well in calculating the polarisation current and electric field distribution, but it is too macroscopic to describe the microscopic behaviours of space charges. The bipolar charge transport model can well simulate the space charge accumulation, but it cannot quantitatively relate the microscopic transport behaviours with the macroscopic conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Our previous research work has shown that below 60°C, the interfacial charge density of the epoxy resin impregnated crepe paper calculated according to the MW model is consistent with the measured value, while above 60°C, it is smaller than the measured value [13]. In order to overcome the shortages of the MW model and bipolar charge transport model, Liang Hucheng, Du Boxue and et al proposed an improved space charge transport model in bi‐layer dielectrics [14].…”
Section: Introductionmentioning
confidence: 98%
“…Our previous research work has shown that below 60°C, the interfacial charge density of the epoxy resin impregnated crepe paper calculated according to the MW model is consistent with the measured value, while above 60°C, it is smaller than the measured value [13]. In order to overcome the shortages of the MW model and bipolar charge transport model, Liang Hucheng, Du Boxue and et al proposed an improved space charge transport model in bi‐layer dielectrics [14].…”
Section: Introductionmentioning
confidence: 98%
“…But, it is noted that the non-linear coefficient α of J 3 is about 1.54 according to the experiment results, which is relatively smaller than the theoretical value (α ¼ 2) in Equation (13). The decrease in α may be caused by the decrease of mobility under extra high electric field, which would be further discussed in the following section.…”
Section: Conduction Mechanism In Xlpe From Low To High Electric Fieldmentioning
confidence: 77%
“…The details of M +θ∆t•K and M-(1-θ)∆t•K can be presented in Equations ( 23) and (24). Where θ = 0, 0.5, 1 is a constant corresponds to forward Euler method, Crank-Nicolson (C-N) method and backward Euler method.…”
Section: Improved Transient Upstream Fem For Solving the Bct Modelmentioning
confidence: 99%
“…The mobility of holes and electrons is assumed as a constant according to [8,11,15]. Classical parameters used for describing the charge activities are selected based on existing researches [19][20][21][22][23][24]. Some parameters (Schottky injection barrier height ω e and ω h , max trapped charge density ρ et0 and ρ ht0 ) in [18] are directly used.…”
Section: Space Charge Distributions Under 2-dimension Plane Modelmentioning
confidence: 99%